2003
DOI: 10.1053/rmed.2002.1425
|View full text |Cite
|
Sign up to set email alerts
|

Cost–effectiveness of salmeterol in patients with chronic obstructive pulmonary disease: an economic evaluation

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with a large economic and social burden. Few economic studies have examined the benefits of inhaled therapy for patients with COPD. This 16-week study examined the cost-effectiveness of salmeterol in this patient group. Patients with a history of COPD were randomised to treatment with salmetrol 50 mcg (229 patients) or placebo (227 patients) twice daily administered by metered-dose inhaler in addition to normal therapy. Forced expiratory volume (FEV1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…[38,48] Estimates of treatment costs have also ranged widely; some studies have not accounted for them at all, [19] and most published studies have used treatment costs per day that were less than half the current average retail price for inhaled controller medications in the US. [15][16][17][18][20][21][22][23][24][25][26][27][28][29] Many studies have described cost effectiveness in terms of cost per QALY gained, which adds another level of assumptions about the progression of COPD and the impact of exacerbations on quality of life. The incidences of exacerbations in our study populations were similar to those reported in most randomized clinical trials and prospective cohorts of COPD patients with moderate and severe COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38,48] Estimates of treatment costs have also ranged widely; some studies have not accounted for them at all, [19] and most published studies have used treatment costs per day that were less than half the current average retail price for inhaled controller medications in the US. [15][16][17][18][20][21][22][23][24][25][26][27][28][29] Many studies have described cost effectiveness in terms of cost per QALY gained, which adds another level of assumptions about the progression of COPD and the impact of exacerbations on quality of life. The incidences of exacerbations in our study populations were similar to those reported in most randomized clinical trials and prospective cohorts of COPD patients with moderate and severe COPD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many studies are based on secondary data collected in randomized clinical trials of highly selected cohorts, which exclude patients with unstable comorbid conditions that commonly affect COPD patients. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Another problem is that individual healthcare cost data are privileged information, so studies have often had to rely on patient interviews or make other uncertain assumptions about the cost and occurrence of exacerbations. Other reports have relied on retrospective comparisons of historical cohorts, which are highly susceptible to selection biases.…”
Section: Introductionmentioning
confidence: 99%
“…For reasons of comparison the authors have used the SGRQ, because it is the most frequently used questionnaire in COPD. There is one other economic evaluation by JONES et al [33] who calculated the costs per patient with a four-unit improvement on the SGRQ. In this study, salmeterol was compared with placebo over 16 weeks in 189 patients with COPD and an incremental costeffectiveness ratio was found of £497 (J785).…”
Section: Discussionmentioning
confidence: 99%
“…There were 16 cost-effectiveness studies that used empirical analysis of clinical trial data of individual patients, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 14 studies that used Markov modelling, [44][45][46][47][48][49][50][51][52][53][54][55][56][57] and eight that used empirical analysis based on observational data. [58][59][60][61][62][63][64][65] Two studies have used a different approach, such as extrapolating the resource use reduction that was obtained after meta-analyses of clinical trials.…”
Section: Methods Usedmentioning
confidence: 99%
“…Eleven studies contributed data on the comparison of salmeterol versus either placebo, [29,39,67] standard therapy, [53] no maintenance therapy [50,55,56] or ipratropium. [45,48,49,61] We discuss these studies together, because, irrespective of how the comparator is labelled, the comparator is in fact short-acting bronchodilator therapy, either used as needed or on a regular basis.…”
Section: Long-acting Inhaled B 2 -Agonist Monotherapymentioning
confidence: 99%